On Informational and Some Other n-Widths of Classes of Analytic Functions in a Disk - Vakarchuk, Sergii; Vakarchuk, Mykhailo (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
In the linear normed spaces , the classes of functions analytic in the circle , , are considered. These classes are defined by averaged moduli of continuity of second order and majorants. The exact values of the informational, linear and Bernstein n-widths of such classes are computed. The optimal method of recovery of functions from indicated classes are found too in the spaces .